USU SOCIAL WELFARE STUDENTS TAKE ORDER CHILDREN TO IMPROVE BASIC READING AND CALCULATING SKILLS (MAHASISWA KESEJAHTERAAN SOSIAL USU AJAK ANAK PANTI MENINGKATKAN KEMAMPUAN DASAR MEMBACA DAN MENGHITUNG) - Elisabet Ronauli Hutapea; Tuti Atika (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Field work practice is a concept of student practice carried out outside campus. In the scope of social welfare, field work practices are carried out in the micro, mezzo, macro scope, using main methods (case work, group work, and community organization and community development) as well as additional methods aimed at restoring the social function of those in need of welfare services. social (PPKS). The USU FISIP Social Welfare Study Program carried out field work practices twice, where the first practice was focused on the micro scope and the second practice was focused on the mezzo and macro scope. The second field work practice was carried out at the Raphael Orphanage. The activities carried out during field work practice 2 focused on increasing interest in reading and counting for elementary school children who were orphans at the Raphael Orphanage. Students are given the freedom to plan programs that can help solve orphanage children's problems related to existing learning. Thus, having practical field work allows students to be able to apply their skills and knowledge in helping students in educational units. The method used is the service learning method, which connects the material and theory obtained and applies it into real action in the form of community service. The method used to solve problems is the groupwork method, which is one of the main methods of social workers.